Copper-catalyzed transfer methylenation via C(sp3)–C(sp3) bond cleavage of alcohols. Issue 23 (13th October 2022) - Hong, Chuan-Ming; Zhuang, Xin; Luo, Zhen; Xiong, Si-Qi; Liu, Zheng-Qiang; Li, Qing-Lin; Zou, Fei-Fei; Li, Qing-Hua; Liu, Tang-Lin
Abstract : Transfer Methylenation: A copper-catalyzed transfer methylenation via the cleavage of unstrained C(sp 3 )-C(sp 3 ) bonds is developted. This is a de novo report for transfer hydrocarbylation between alcohols and carbonyl compounds. Abstract : Transfer hydrogenation between alcohols and carbonyl compounds via C–H bond cleavage is well known, whereas transfer hydrocarbylation remains a challenge due to the cleavage of the unactivated C–C bond. Herein, we disclose a transfer methylenation approach towards various secondary and tertiary alcohols from abundant chemical feedstocks. To the best of our knowledge, this is a de novo report of transfer methylenation via copper-catalyzed β-carbon elimination to cleave the C(sp 3 )–C(sp 3 ) bond of tertiary alcohols. This reaction features a broad substrate scope and good functional group tolerance towards sensitive functional groups (carboxylic esters, cyano group, etc .) and can be scaled up, making it an environmentally friendly and step-economical procedure. Meanwhile, the catalytic system exhibits high reactivity (up to 400 TON), and also allows for the late-stage functionalization of a series of bioactive and functional material molecules. Mechanistic studies indicate that the reaction involves a copper–alkoxide–pyridine intermediate.